Implementation of strengthening character education in Indonesian elementary schools: systematic literature review - Andi Jusmiana; Herianto Herianto; Marina Gusnia Ruchiyat (Arshaka: Social Sciences and Education, 2026)
This study examines the implementation of Strengthening Character Education (PPK) in Indonesian elementary schools through a systematic approach. The study analyzed 18 relevant studies to understand implementation strategies, character values developed, and challenges and opportunities in character education. The results showed that PPK was implemented through curriculum integration, extracurricular activities, collaboration between teachers, parents, and the community, as well as the use of media and technology. The most prominent character values include mutual cooperation, religiosity, integrity, independence, and nationalism. The main obstacles include a dense curriculum, limited teacher training, and suboptimal communication. Nevertheless, cross-stakeholder collaboration and government program support provide opportunities to strengthen character education in a sustainable manner. This research provides an empirical basis for the development of character education strategies that are effective, contextual, and adaptive to local culture.